10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Delays in cancer diagnosis and treatment pose significant challenges to the efficiency and equity of universal health systems. Patient navigation programs have been introduced to improve care coordination and facilitate timely access to treatment; however, evidence on their cost implications remains limited, particularly in middle-income countries. This study evaluates the impact of Brazil's National Breast Cancer Patient Navigation Program on waiting times and treatment costs within the Unified Health System (SUS). Exploiting the nationwide implementation of the program in January 2023, we use administrative microdata covering January 2021 to June 2024. Gynecological cancers are used as a comparison group because they affect the same population and rely on similar hospital resources. Causal effects are estimated using the Synthetic Difference-in-Differences (SDID) approach. The results indicate that patient navigation reduced waiting time between diagnosis and radiotherapy initiation by approximately 10 days relative to the comparison group, while effects on surgery and chemotherapy were limited. At the same time, radiotherapy costs increased by about 16.5 percent, suggesting a short-term expansion in service utilization reflecting previously unmet demand. The effects are heterogeneous across regions, with larger improvements observed in more developed areas. Overall, the findings indicate that patient navigation can improve access to breast cancer treatment but that its effectiveness depends on the availability of healthcare resources.